Chronic venous disease. Part 2: diagnosis and treatment. (1st July 2022) - Das, Anupam; Sil, Abheek; Kumar, Piyush; Neema, Shekhar
Summary: Chronic venous disease (CVD) is a common medical condition that results from venous hypertension of the limbs, leading to significant morbidity. The diagnosis is quite straightforward from patient history and obvious clinical manifestations. In the recent past, the availability of various invasive and noninvasive treatments has assisted in evaluation of such cases. Although compression therapy is the mainstay of management, newer surgical and other interventional techniques are now being considered for patients who do not respond to conventional medical management. The second part of this two‐part review article will outline a diagnostic approach in cases of CVD and discuss the management principles encompassing conservative, pharmacological and interventional options. Abstract : Although compression therapy is the mainstay of management of chronic venous disease (CVD), newer surgical and other interventional techniques are now being considered for patients who do not respond to conventional medical management. This review article will outline a diagnostic approach in cases of CVD and discuss the management principles encompassing conservative, pharmacological and interventional options.